Fibroblast Growth Factor 23 and Left Ventricular Hypertrophy in Chronic Kidney Disease—A Pediatric Perspective - Grund, Andrea; Sinha, Manish D.; Haffner, Dieter; Leifheit-Nestler, Maren (Frontiers in Pediatrics, 2021)
Cardiovascular diseases (CVD) are a hallmark in paediatric patients with chronic kidney disease (CKD) contributing to an enhanced risk of all-cause and CV morbidity and mortality in these patients. The bone-derived phosphaturic hormone fibroblast growth factor (FGF) 23 progressively rises with declining kidney function to maintain phosphate homeostasis. Up to 1000-fold increase in patients with kidney failure, FGF23 is associated with the development of left ventricular hypertrophy (LVH) and thereby accounts to be a CVD risk factor in CKD. Experimentally, FGF23 directly induces hypertrophic growth of cardiac myocytes in vitro and LVH in vivo with clinical studies in adult CKD have observed cardiotoxicity associated with FGF23. Data regarding prevalence and determinants of FGF23 excess in children with CKD are limited. This review summarizes current data and discusses whether FGF23 may be a key driver of LVH in paediatric CKD.